Social media use and its impact on adolescent mental health: An umbrella review of the evidence. (April 2022) - Valkenburg, Patti M.; Meier, Adrian; Beyens, Ine
Abstract: Literature reviews on how social media use affects adolescent mental health have accumulated at an unprecedented rate of late. Yet, a higher-level integration of the evidence is still lacking. We fill this gap with an up-to-date umbrella review, a review of reviews published between 2019 and mid-2021. Our search yielded 25 reviews: seven meta-analyses, nine systematic, and nine narrative reviews. Results showed that most reviews interpreted the associations between social media use and mental health as 'weak' or 'inconsistent, ' whereas a few qualified the same associations as 'substantial' and 'deleterious.' We summarize the gaps identified in the reviews, provide an explanation for their diverging interpretations, and suggest several avenues for future research.